3D printing of high‐purity silicon carbide. Issue 3 (19th November 2019) - Terrani, Kurt; Jolly, Brian; Trammell, Michael
Abstract: A method for advanced manufacturing of silicon carbide offering complete freedom in geometric complexity in the three‐dimensional space is described. The method combines binder jet printing and chemical vapor infiltration in a process capable of yielding a high‐purity, fully crystalline ceramic—attributes essential for ideal performance in very high‐temperature applications or in the presence of displacement damage. Thermal conductivity and characteristic equibiaxial flexural strength of the resulting monolithic SiC at room temperature are 37 W·(m·K) −1 and 297 MPa, respectively.